Attention modulates maintenance of representations in visual short-term memory. - Kuo, B; Stokes, M; Nobre, A (2012)
Recent studies have shown that selective attention is of considerable importance for encoding task-relevant items into visual short-term memory (VSTM) according to our behavioral goals. However, it is not known whether top-down attentional biases can continue to operate during the maintenance period of VSTM. We used ERPs to investigate this question across two experiments. Specifically, we tested whether orienting attention to a given spatial location within a VSTM representation resulted in modulation of the contralateral delay activity (CDA), a lateralized ERP marker of VSTM maintenance generated when participants selectively encode memory items from one hemifield. In both experiments, retrospective cues during the maintenance period could predict a specific item (spatial retrocue) or multiple items (neutral retrocue) that would be probed at the end of the memory delay. Our results revealed that VSTM performance is significantly improved by orienting attention to the location of a task-relevant item. The behavioral benefit was accompanied by modulation of neural activity involved in VSTM maintenance. Spatial retrocues reduced the magnitude of the CDA, consistent with a reduction in memory load. Our results provide direct evidence that top-down control modulates neural activity associated with maintenance in VSTM, biasing competition in favor of the task-relevant information.